2019
DOI: 10.1103/physrevlett.122.241602
|View full text |Cite
|
Sign up to set email alerts
|

From the Weyl Anomaly to Entropy of Two-Dimensional Boundaries and Defects

Abstract: We study whether the relations between the Weyl anomaly, entanglement entropy (EE), and thermal entropy of a two-dimensional (2D) conformal field theory (CFT) extend to 2D boundaries of 3D CFTs, or 2D defects of D ≥ 3 CFTs. The Weyl anomaly of a 2D boundary or defect defines two or three central charges, respectively. One of these, b, obeys a c-theorem, as in 2D CFT. For a 2D defect, we show that another, d2, interpreted as the defect's "conformal dimension," must be non-negative if the Averaged Null Energy Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(117 citation statements)
references
References 56 publications
13
97
0
Order By: Relevance
“…We numerically verified that this boundary condition agrees with the procedure described in [16] as well as the more recent discussion in [38]. The fact that the RT surfaces should end orthogonally on the RS brane has also been made from the point of view of the replica method in [39].…”
Section: Jhep09(2020)121supporting
confidence: 84%
“…We numerically verified that this boundary condition agrees with the procedure described in [16] as well as the more recent discussion in [38]. The fact that the RT surfaces should end orthogonally on the RS brane has also been made from the point of view of the replica method in [39].…”
Section: Jhep09(2020)121supporting
confidence: 84%
“…This implies, in particular, that d 1 0. Furthermore, assuming the validity of the averaged null energy condition in the presence of a defect one can prove that d 2 0 [70]. Crucially, in section 2.1 we have shown that, for any supersymmetric surface defect…”
Section: Weyl Anomaly Coefficientsmentioning
confidence: 74%
“…where we use p to indicate the defect dimension and q for the codimension. We also used the relation between d 2 and h in arbitrary dimension [70]. For the Wilson surface defect in d = 6 this gives C D = 80πh 3 , a result that was confirmed by a free theory computation for the theory of a single free tensor multiplet [71] and that is not valid for a free non-supersymmetric theory [72].…”
Section: Comparison With Holography and Higher Codimensionmentioning
confidence: 94%
“…A computation in ref. [26] shows that the corresponding boundary a-anomaly is independent of marginal parameters, at least at leading order in a large 't Hooft coupling expansion. However, as shown in [27], the corresponding one-point functions of the marginal operators vanish in this limit as well, consistent with our result.…”
Section: Discussion and Examplesmentioning
confidence: 90%